Ten Drivers of the Chinese Digital Miracle - G. G. Goloventchik; Yanhai He (Цифровая трансформация, 2021)
The digital economy of the People's Republic of China has achieved great success, as a result of which China, together with the United States, have become world leaders in digitalization. China's rapid digital development model has become an example and a model for the rest of the world. The paper analyzes in detail the ten drivers of Chinese digital success, provides extensive up-to-date statistical data.